Effect of oat or rice flour on pulse-induced gastrointestinal symptoms and breath hydrogen in subjects sensitive to pulses and controls - a randomised cross-over trial with two parallel groups - Laito Salla; Valkonen Niina; Laaksonen Oskar; Kalliomäki Marko; Tuure Tuula; Linderborg Kaisa M (CAMBRIDGE UNIV PRESS, 2025)
Pulses are healthy and sustainable but induce gut symptoms in people with a sensitive gut. Oats, on the contrary, have no fermentable oligo- di-, monosaccharides and polyols compounds and are known for the health effects of their fibres. This 4-day cross-over trial investigated the effects of oat and rice flour ingested with pulses on gut symptoms and exhaled gases (4th day only) in subjects with a sensitive gut or IBS (n 21) and controls (n 21). The sensitive group perceived more symptoms after both meals than controls (P = 0 center dot 001, P = 0 center dot 001). Frequency, intensity or quality of the symptoms did not differ between meals during the first 3 d in either group. More breath hydrogen was produced after an oat than rice containing meal in both groups (AUC, P = 0 center dot 001, P = 0 center dot 001). No between-group difference was seen in breath gases. During day 4, both sensitive and control groups perceived more symptoms after the oat flour meal (P = 0 center dot 001, P = 0 center dot 0104, respectively) as mainly mild flatulence. No difference in moderate or severe symptoms was detected. Increased hydrogen production correlated to a higher amount of perceived flatulence after the oat flour meal in both the sensitive and the control groups (P = 0 center dot 042, P = 0 center dot 003, respectively). In summary, ingestion of oat flour with pulses increases breath hydrogen levels compared with rice flour, but gastrointestinal symptoms of subjects sensitive to pulses were not explained by breath hydrogen levels. Additionally, consumer mindsets towards pulse consumption and pulse-related gut symptoms were assessed by an online survey, which implied that perceived gut symptoms hinder the use of pulses in sensitive subjects.